Bacterial Sepsis in Patients with Visceral Leishmaniasis in Northwest Ethiopia. (6th May 2014) - Endris, Mengistu; Takele, Yegnasew; Woldeyohannes, Desalegn; Tiruneh, Moges; Mohammed, Rezika; Moges, Feleke; Lynen, Lutgarde; Jacobs, Jan; van Griensven, Johan; Diro, Ermias
Abstract : Background and Objectives . Visceral leishmaniasis (VL) is one of the neglected diseases affecting the poorest segment of world populations. Sepsis is one of the predictors for death of patients with VL. This study aimed to assess the prevalence and factors associated with bacterial sepsis, causative agents, and their antimicrobial susceptibility patterns among patients with VL. Methods . A cross-sectional study was conducted among parasitologically confirmed VL patients suspected of sepsis admitted to the University of Gondar Hospital, Northwest Ethiopia, from February 2012 to May 2012. Blood cultures and other clinical samples were collected and cultured following the standard procedures. Results . Among 83 sepsis suspected VL patients 16 (19.3%) had culture confirmed bacterial sepsis. The most frequently isolated organism was Staphylococcus aureus (68.8%; 11/16), including two methicillin-resistant isolates (MRSA). Patients with focal bacterial infection were more likely to have bacterial sepsis (P < 0.001 ). Conclusions . The prevalence of culture confirmed bacterial sepsis was high, predominantly due to S. aureus . Concurrent focal bacterial infection was associated with bacterial sepsis, suggesting that focal infections could serve as sources for bacterial sepsis among VL patients. Careful clinical evaluation for focal infections and prompt initiation of empiric antibiotic treatment appears warranted in VL patients.